The Role of Surau Godang in Improving Religious Literacy: Study at the Minangkabau Community in West Sumatra - Shalahuddin Al Syaifullah; Syamsul Arifin; Nafik Muthohirin (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to examine the role of Surau Godang in the process of forming community religious literacy which is integrated with the local wisdom values of the residents of Jorong, Kociak City, West Sumatra. Various religious literacy taught to children, youth, and parents is carried out in various forms, such as memorization of the Qur'an, regular religious submissions, silek (silat), youth seminars, and others. This article also analyzes the effectiveness of Islamic science learning methods in shaping the morals of the community and what challenges and opportunities are faced by the Surau Godang in forming the morals of Minangkabau youth. This research was conducted using a case study approach in Jorong Koto Kocyak, West Sumatra. Meanwhile, the data collection technique uses interview, observation, and documentation methods. The results of the study concluded several religious literacy activities that support the moral formation of Muslims, including routine recitation attended by elderly groups, as well as Qur'an memorization activities, pencak silat (silek), and religious group discussions for children and youth.